(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Bondar L. V. Strategic competence of future engineers in the context of the teaching foreign language for Specific Purposes current problems. The present article deals with prerequisites for the strategic competence formation of engineering students in learning French professionally oriented monologue speech. Іt was determined that process of professionally oriented language learning is associated with psycho- and linguocognitive peculiarities specific for future engineers which are reflected in information transmission structures, its perception, treatment re/production dominance modes. These peculiarities are reflected in learning strategies and have the influence on mastering French professionally oriented monologue-argumentation effectiveness.